2008
DOI: 10.1007/s11426-008-0134-0
|View full text |Cite
|
Sign up to set email alerts
|

Protonation effects on electron transport through diblock molecular junctions: A theoretical study

Abstract: Diblock oligomers are widely used in molecular electronics. Based on fully self-consistent nonequilibrium Green ' s function method and density functional theory, we study the electron transport properties of the molecular junction with a dipyrimidinyl-diphenyl (PMPH) diblock molecule sandwiched between two gold electrodes. Effects of different kinds of molecule-electrode anchoring geometry and protonation of the PMPH molecule are studied. Protonation leads to both conductance and rectification enhancements. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…However, to our knowledge, the mechanism for the effect of protonation on charge transport through a molecule is not fully revealed. The numerical simulation by Li et al only exhibited an enhanced rectification by protonation, while inversion of the rectifying direction was not demonstrated. Thus, a further study is highly required to understand the protonation effects.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, to our knowledge, the mechanism for the effect of protonation on charge transport through a molecule is not fully revealed. The numerical simulation by Li et al only exhibited an enhanced rectification by protonation, while inversion of the rectifying direction was not demonstrated. Thus, a further study is highly required to understand the protonation effects.…”
Section: Introductionmentioning
confidence: 92%
“…The Perdew–Burke–Ernzerhof (PBE) exchange-correlation functional is used for the generalized gradient approximation (GGA) . To save the computational effort, we employ a single-ζ plus polarization (SZP) basis set for Au atoms and a double-ζ plus polarization (DZP) basis set for the other atoms except for proton atoms. , The cutoff radii of the pseudoatomic orbitals are fixed by an energy shift parameter of 100 meV, and a 300 Ry mesh cutoff is chosen. The convergence criterion for the density matrix is chosen as 10 –4 .…”
Section: Theoretical Model and Computational Detailsmentioning
confidence: 99%
“…9,10 Furthermore, experiment has found that the rectifying is independent of the temperature in the range between 300 and 50 K. 11 Understanding the mechanism of the rectifiers has been the subject of a great deal of theoretical works. 12−16 The factors affecting the rectification properties, such as protonation of the molecule in acid solution 17,18 and the effect of the molecular length 19,20 have been further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, diblock co-oligomer diodes with donor–acceptor (D–A) structure have captured a lot of attention as promising intrinsic molecular diodes. It has been reported that a clear and reproducible rectification can be achieved and the rectifying direction can be controlled by adjusting the molecular orientation. , Furthermore, experiment has found that the rectifying is independent of the temperature in the range between 300 and 50 K . Understanding the mechanism of the rectifiers has been the subject of a great deal of theoretical works. The factors affecting the rectification properties, such as protonation of the molecule in acid solution , and the effect of the molecular length , have been further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric molecule-electrode contacts include asymmetric terminal anchoring groups, molecule-electrode contact configurations, and electrode materials. It has been found that the rectifying properties of devices can be fine-tuned by changing the molecular length 11 12 , terminal anchoring groups 13 14 15 , side groups 12 , molecule-electrode contact configurations 16 17 18 , the acid-base property of the solution 7 19 20 , and the external potential field 21 .…”
mentioning
confidence: 99%